Observed poleward shift of the South Equatorial Current and associated thermohaline variations in the South Pacific subtropical gyre - Jingxuan Sun; Linlin Zhang (Geoscience Letters)
Abstract The meridional shift of the Pacific South Equatorial Current (SEC) and the thermohaline variability in the South Pacific subtropical gyre during 1960–2020 are investigated using observational datasets. As the northern limb of the gyre circulation, the southern branch of the SEC has shifted poleward at a rate of approximately 0.17°/decade between 170°E and 140°W, but has no intensification in the zonal volume transport. This shift is reflected in the poleward shift of the basin-scale easterly winds, and consequently a southward migration of the SEC through the baroclinic Rossby wave adjustments. Such poleward shift in easterlies is proposed tightly relevant to the intensification of the Southern Annular Mode. A 1.5–layer reduced gravity model is then adopted to provide a dynamic framework that helps our understanding of these observed changes. Meanwhile, the steric height in the South Pacific subtropical gyre region exhibits a linearly upward trend, and contributions from haline contraction is comparable to thermal expansion between 20° and 40°S at 500–1000 m, underscoring a significant role of salinity modifications in the subsurface ocean. Further analysis indicates that the halosteric component change is related to the widespread freshening in the Southern Hemisphere over the past decades.